Immigration and theology of vocation. Issue 3 (13th July 2021) - Sánchez M., Leopoldo A.
Abstract: Contemporary reflection on immigration can benefit from a Lutheran theology of vocation. A vocational lens serves as a critical and constructive tool to examine hospitality, legal, and relational approaches to migration today. After offering a brief survey of current theological and ethical approaches to migration by U.S. authors, the article argues for a complementary vocational approach to migration as the most comprehensive proposal accounting for the complexity of the immigration debate in our thinking and action concerning immigrant neighbors. The article deals with the strengths and limits of the proposed vocational approach.